Land markets in Europe: Institutions and market outcomes - Pavel Ciaian; D'Artis Kancs; Dušan Drabik (Economics and Econometrics Research Institute (EERI), 2016)
In this chapter, we review land market institutions in the European Union (EU) and their potential impact on land markets. We first review land tenure-/ownership regulations and find that they vary heavily across EU Member States. Four types of tenure-/ownership measures are implemented in the EU: to protect the tenant, to protect the owner, to protect the (non-farm) land owner, and to prevent land fragmentation. We then examine EU land-related environmental regulations whose general objective is to address land market failures linked to externalities and the provision of public goods. Despite possibly reducing private benefits of land owners or users, environmental regulations may generate welfare gains to society by improving the environmental services on land. Finally, we investigate how area-based subsidies affect land prices. These subsidies are empirically found to be partially capitalized into land values, albeit at a lower rate than suggested by theory.
Keywords: H22; L11; Q11; Q12; Q15; Q18; P32; R12; 330; Land markets; institutions; tenure; ownership; externalities; public goods